The effect of solid carriers in fluidized bed for fenton process in treating recalcitrant wastewaters / Mustapha Mohammed Bello - Mustapha , Mohammed Bello (2018)
Fluidized bed Fenton (FBF) process is a modification of Fenton oxidation that can reduce sludge generation and enhance process performance. The fluidized solid carriers can enhance mass transfer and provide surface for the precipitation of iron oxide, thus reducing sludge generation. Furthermore, the iron oxide-coated carrier can act as a heterogeneous Fenton catalyst, further enhancing process performance. Despite the potentials of FBF process, many aspects of the process, such as the effect of carrier and its possible interaction with Fenton’s reagent are yet to be fully established. Considering the importance of carrier on the process performance, understanding its effect and interaction with Fenton’s reagent/pollutants is necessary for effective optimization of the process. Thus, this study is aimed at filling these gaps through theoretical and experimental approaches. A fluidized bed Fenton process was developed and its performance was evaluated through the degradation of a model pollutant, Reactive Black 5 (RB5). The FBF process was first optimized using SiO2 as the carrier. Quantum chemical calculations was then used to predict the possible interactions among the SiO2, Fenton’s reagent and RB5. The results of the quantum chemical calculations were subsequently validated through experimental investigations of the effect of SiO2 and interaction with the Fenton’s reagent. To further enhance the cost-effectiveness of the FBF process, the feasibility of using a palm kernel shell granular activated carbon (PKSGAC) as an alternative low-cost carrier was investigated. The performance of the PKSGAC was compared with that of SiO2. Using SiO2, the FBF process can remove 80% of the initial COD and more than 99% of the initial color under optimum conditions. This COD removal was about 15 to 20% higher than conventional Fenton oxidation. Under constant SiO2 loading, the most significant parameters affecting the FBF process are the initial concentration of Fe2+ and the concentration of the pollutant. The analysis of quantum chemical parameters shows that there are possible interactions between SiO2, Fenton’s reagent and the pollutant. For example, with a comparatively higher EHOMO of -8.72 eV, SiO2 shows a tendency to donate electrons to Fe3+ (EHOMO = -18.74 eV), which explains the crystallization of iron oxide on the carriers. Analysis of frontier orbitals also shows that SiO2 can take up electrons from H2O, H2O2, and H3O+ molecules due to its lower energy. Analysis of enthalpy and Gibb’s free energies further revealed that beside crystallization of iron oxide, other interactions such as complexation between SiO2 and H2O2, can occur in the process. These results are supported by the experimental results and surface analysis of the carrier. The overall results show that solid carriers contribute to the removal of pollutants through adsorption and may also form complexes with H2O2. However, due to the synergy of oxidation and adsorption, the overall process performance is enhanced in the presence of solid carriers. Comparing the PKSGAC with SiO2, PKSGAC offers a higher performance in terms of treatment efficiency and hydrodynamic characteristics, making it a potential alternative to the commonly used carrier.